Strategi Manajemen Kepala Sekolah dalam Upaya Penerapan Mutu Pendidikan - Mulyani; Abdul Kosim; Kasja Eki Waluyo (CENDEKIA, 2022)
The principal is the most important role in the realization of the quality of education, therefore the purpose of this study 1) to find out how the description of the conditions of the implementation of the principal's leadership in carrying out the function to improve school quality, 2) to find out how school achievement can be achieved, 3) to find out the role leadership of the principal to face obstacles in carrying out their duties. The research method used is descriptive qualitative research. Data collection was obtained from information, places and activities of the principal's leadership activities, as well as documents. Data collection techniques in the form of in-depth interviews, direct observation, and recording documents. The results of the study are in the form of main findings, namely: 1) improving the quality of learning at MA Yaspia Cibogo is determined how the principal can manage school management and the ability to set the vision, mission, educational goals of MA Yaspia Cibogo, strategies, and targets appropriately according to the situation and conditions school. 2) improving the quality of the principal's leadership competence in carrying out his duties and functions is largely determined by the principal's self-motivation and how to manage learning inputs, organize learning processes, and produce learning outputs. 3) the overall condition of the principal of MA Yaspia Cibogo in carrying out his duties and functions as an educator (educator), as a manager, as an administrator, as a supervisor, as a leader (leader), as an innovator, as a very good multifactor so that the principal can be an example in carrying out their duties.